Status Dan Perlindungan Hukum Tanah Magersari Di Lingkungan Kraton Yogyakarta - Kevin Notario Raja Dolok; Fifiana Wisnaeni (Magister Kenotariatan Universitas Diponegoro, 2022)
AbstractTanah Magersari is a land owned by the Sultanate and the Duchy which is widely used by people in the Special Region of Yogyakarta to become a place of residence or business. Tanah Magersari can only be used by indigenous people based on the Rijksblad Sultanate 1918 Number 16 jo. 1925 No.23, and Rijksblad 1918 No.18 jo Rijksblad 1925 Number 25. The purpose of this study is to determine the ownership status of Tanah Magersari in the Sultan's Palace in terms of national land law and legal protection given to Tanah Magersari rights holders. Based on the results of the study it is known that: 1. The status of Tanah Magersari within the Ngayogyakarta Hadiningrat Sultanate Palace based on the laws and regulations of Yogyakarta is the land of the Sultanate and the Duchy has been declared a legal entity, so the Sultanate has ownership rights over the Sultanate's land and the Duchy has ownership of the Duchy land . 2. Legal protection granted to holders of Tanah Magersari rights is based on Special Regional Regulations and Basic Agrarian Laws.Keywords: legal status; legal protection; tanah magersariAbstrakTanah magersari adalah tanah kepunyaan Kasultanan dan Kadipaten yang sering dipergunakan masyarakat di Daerah Istimewa Yogyakarta sebagai tanah hunian atau untuk wirausaha. Tanah magersari hanya dapat dipergunakan masyarakat asli didasarkan Rijksblad Kesultanan 1918 Nomor 16 jo. 1925 No.23, serta Rijksblad 1918 No.18 jo Rijksblad 1925 Nomor 25. Tujuan penelitian ini gar diketahui pemilik sah dari tanah magersari di daerah Kraton Yogyakarta dilihat dari hukum tanah nasional serta perlindungan hukum yang diserahkan pada pemegang hak tanah magersari. Berdasarkan hasil penelitian diketahui bahwa : 1. Status tanah magersari dalam lingkungan Keraton Kasultanan Ngayogyakarta Hadiningrat berdasarkan peraturan perundang-undangan Yogyakarta adalah tanah Kasultanan dan Kadipaten sudah dinyatakan sebagai badan hukum, menyebabkan Kasultanan mempunyai hak milik dari tanah Kasultanan serta Kadipaten mempunyai hak milik dari tanah Kadipaten. 2. Perlindungan hukum yang diserahkan pada pemegang hak dari tanah magersari adalah didasarkan Peraturan Daerah Istimewa dan Undang-undang Pokok Agraria.Kata kunci : status hukum; perlindungan hukum; tanah magersari